Preparation and dielectric properties of (Sr1-xCa x)Fe0.5Nb0.5O3; (x=0.0, 0.1, 0.2) ceramics - Thanatep Phatungthane (2018)
In the present work, strontium calcium iron niobate ((Sr1-xCax)Fe0.5Nb0.5O3; SCFN) (x=0, 0.1, and 0.2) powders were synthesized for the first time using a molten salt technique. The pure phase perovskite obtained at a relative low calcination temperature of 800 °C was characterized using the X-ray diffraction technique (XRD). SCFN ceramics were fabricated and their properties were investigated. The XRD data of the SCFN ceramics was consistent with an orthorhombic symmetry. However, the solubility of Ca in the SCFN ceramics had an upper limit at x=0.1. All ceramics showed a large dielectric constants. The Ca doping inhibited grain growth, but produced an improvement in dielectric-temperature stability. Furthermore, the doping reduced loss tangent, especially for the x=0.1 sample. These results suggest that the SCFN ceramics prepared from molten salt synthesis exhibit a good dielectric performances, compared to many high dielectric materials that have been prepared using the conventional method. © 2012 Elsevier Ltd and Techna Group S.r.l.